The collected works (gsuṅ ʼbum) of Śākya-rin-chen, the ninth Rje Mkhan-po of Bhutan - Śākya-rin-chen, Rje Mkhan-po, 1710-1759 (Kunzang Topgey, 1976)
Writings of famed Bhutanese polymath of the Drukpa Kargyudpa tradition.